Bioprospecting of endophytic actinobacterium associated with Aloe ferox mill for antibacterial activity - Tsolanku Sidney Maliehe; Melusi Mbambo; Londeka Sibusisiwe Ngidi; Jabulani Siyabonga Emmanuel Shandu; Ofentse Jacob Pooe; Peter Masoko; Tlou Nelson Selepe (BMC, 2022)
Abstract Background The emergence of drug resistance among pathogens has resulted in renewed interest in bioprospecting for natural microbial products. Methods This study aimed to bioprospecting endophytic actinobacterium associated with Aloe ferox Mill for its antibacterial activity. Endophytic actinomycetes were isolated from the gel of A. ferox Mill by surface sterilization technique using actinomycete isolation agar. The isolate with a promising antibacterial activity was identified using 16S rRNA sequence analysis. The minimum inhibitory concentration (MIC) of the extract was assessed by the micro-dilution method and its effect on the respiratory chain dehydrogenase (RCD) activity was ascertained by the iodonitrotetrazolium chloride (INT) assay. Fourier transform-infrared spectrophotometer (FTIR) and gas chromatography-mass spectrophotometry (GC-MS) were employed to identify functional groups and the chemical constituents, respectively. Results The actinobacterium was found to be Streptomyces olivaceus CP016795.1. Its extract displayed noteworthy antibacterial activity (MIC ≤1 mg/mL) against Staphylococcus aureus (ATCC 25925), Bacillus cereus (ATCC 10102), and Escherichia coli (ATCC 25922); and showed an inhibitory effect on the RCD activity. FTIR spectrum displayed hydroxyl, amine, and aromatic groups, and the GC-MS revealed 5-Hydroxymethylfurfural as the main constituent (19.47%). Conclusions S. olivaceus CP016795.1 can serve as a potential source of effective antibacterial compounds.